Science in seconds for kids : over 100 experiments and activities you can do in ten minutes or less - Stier, Sam; Potter, Jean, 1947- (Hoboken, N.J. : Jossey-Bass, 2021)
"Do you want to learn to make lightening in a room, keep paper dry under water, and see colors that aren't there? Experience the magic of science with these quick, easy experiments and activities. You can complete each activity in just ten minutes or less, and the clear step-by-step instructions and illustrations help you get it right every time. You will find most of the required materials already in your home! With illustrations, full-color pages, concise material lists, and easy-to-understand instructions, the second edition of Science in Seconds makes learning fun and practical. The activities will cover several different subject areas, including air, animals, colors, gravity, energy, light, machines, the human body, magnetism, and weather. Before you know it, kids will be making rainbows on the floor, popping balloons with magnifying glasses, and bending water from the faucet."--
Includes index.
Keywords: Science -- Experiments -- Juvenile literature